Targets of the transcriptional repressor oncoprotein Gfi-1 - Duan, Zhijun (The National Academy of Sciences, 2003)
Gfi-1 is a zinc finger transcriptional repressor originally recognized for its role in T cell differentiation and lymphomas. Recent experiments reveal that gene-targeted Gfi-1-deficient mice are neutropenic and that Gfi-1 mutations cause human neutropenia. In both cases, myeloid progenitor cells lose the ability to distinctly differentiate granulocytes from monocytes. The molecular mechanism of the hematopoietic abnormalities caused by Gfi-1 deficiency remains undetermined because of a lack of known Gfi-1 target genes. To identify Gfi-1 targets in vivo, we performed large-scale chromatin immunoprecipitation analysis on a set of 34 candidate genes in myeloblast (KG-1 and HL-60), monoblast (U937), and T lymphocyte cell lines (Jurkat), in concert with RT-PCR-based expression profiling. We identified 32 Gfi-1 binding sites in a functionally variable set of 16 genes, including complements of cell-cycle regulators, transcription factors, and granulocyte-specific markers. Cluster analysis of expression patterns and chromatin immunoprecipitation data reveals that Gfi-1 targets a subset of genes differentiating hematopoietic lineages and therefore plays a relatively superior role in the hierarchy of factors governing stem cell differentiation.